Acetobacteraceae as exopolysaccharide producers: Current state of knowledge and further perspectives - Wünsche, Julia; Schmid, Jochen (Frontiers in Bioengineering and Biotechnology, 2023)
Exopolysaccharide (EPS) formation against harmful biotic and abiotic environmental influences is common among bacteria. By using renewable resources as a substrate EPSs represent a sustainable alternative to fossil-based polymers as rheological modifiers in food, cosmetics, and pharmaceutical applications. The family of Acetobacteraceae, traditionally associated with fermented food products, has demonstrated their ability to produce a wide range of structural and functional different polymers with interesting physicochemical properties. Several strains are well known for their production of homopolysaccharides of high industrial importance, such as levan and bacterial cellulose. Moreover, some Acetobacteraceae are able to form acetan-like heteropolysaccharides with a high structural resemblance to xanthan. This minireview summarizes the current knowledge and recent trends in both homo- and heteropolysaccharide production by Acetobacteraceae.